“Our apple is what Eve eats”: Manoel de Barros' poetics and the epistemic places of undisciplined museologies in Brazil (Cadernos de Sociomuseologia, 2020)
Clovis Carvalho BrittoDepartamento de Museologia, Universidade Lusófona de Humanidades e TecnologiasTese de Doutoramento (2019)Abstract The thesis investigates the tendencies of museological thought that guide Museologies in Brazil and the debates around its epistemological foundations. It proposes an outline of a 'social history of the emergence of problems' having as a methodology the examination of the 'theory of practice' of the Indisciplined Museologies. It performs a metalinguistic reading when museologically thinking about Museologies, having as theoretical reference the poetics of the Brazilian writer Manoel de Barros (1916-2014) in the verification of the 'deslimites' that originated new spaces of experience and paradigmatic changes. Performs mapping epistemic transformations in Brazilian Museologies, with emphasis on the analysis of intellectual trajectories and paradigms that conformed the New Museology and Social Museology. In order to do so, it explains the 'constellations of commitment' and 'shared examples' that produced 'scientific revolutions' in Museologies, from the examination of museums at the service of collections, of communities and of differences. The thesis examines the strategies of resistance, militancy and institutionalization of Social Museology in Brazil, through a sociomuseological analysis of its intellectual references. In these terms, investigates the itineraries of some of the main responsible for these transformations, especially the trajectory of the museologist Mario de Souza Chagas. It demonstrates how the investigation of tendencies of thought marked by epistemic disobediences forged in the scope of Museologies, like the Social Museology as paradigmatic change and Sociomuseology as School of Thought, raises proposals that point to 'descomeços' in the understanding of poetic crossings (creative power) and political (power of resistance). Keywords: Indisciplined Museologies; Social Museology; Sociomuseology; Paradigms; Manoel de Barros.